Prolidase activity in women with polycystic ovarian syndrome undergoing assisted conception - Kadriye Erdoğan; Emine Utlu Özen; İnci Kahyaoğlu; Salim Neselioglu; Özcan Erel; Serra Akar; Özhan Özdemir; Cihangir Mutlu Ercan; Yaprak Engin Üstün (Journal of Obstetrics and Gynaecology)
Background Prolidase is a manganese (Mn)-dependent cytosolic exopeptidase that degrades imidodipeptides with C-terminal proline or hydroxyproline. Prolidase recycling from imidodipeptides plays a critical role in collagen resynthesis and extracellular matrix (ECM) remodelling. Following an increase in gonadotropins, ovarian and follicular collagen undergo substantial degradation. Abnormal ovarian ECM composition is associated with polycystic ovary syndrome (PCOS). This study aimed to examine prolidase activity in the serum and follicular fluid (FF) of women undergoing in vitro fertilisation/intracytoplasmic sperm injection (IVF/ICSI) treatment, comparing those with PCOS to those with normal ovarian function.Methods This prospective study enrolled 50 participants, of whom 44 were included. PCOS diagnosis followed the Rotterdam consensus criteria, with 20 patients constituting the study group. The control group comprised 24 individuals with mild-to-moderate male infertility. Prolidase enzyme activity in serum and FF was measured using the Chinard reagent via spectrophotometric analysis and compared between the groups.Results Serum and FF prolidase levels were significantly lower in patients with PCOS (p < 0.05). A direct correlation was observed between serum and FF prolidase levels (p < 0.05). Although blastocyst quality scoring (BQS) significantly decreased in PCOS patients, no statistical difference was observed in the clinical pregnancy rate between the groups (p < 0.05) (p > 0.05). A negative correlation existed between serum prolidase levels and total antral follicle (AF) count (p < 0.05). Conversely, both serum and FF prolidase levels positively correlated with BQS (r = 0.574)(p < 0.05) (r = 0.650)(p < 0.05).Conclusions Patients with PCOS showed lower serum and FF prolidase levels, indicating abnormal degradation of ovarian and follicular collagen, potentially causing anovulation.